Renewable Energy Revolution: Mapping Global Trends and Future Directions - Vishant Kumar Meena; Aman Khan; Gaurav Jain (International Journal of Environmental Noise and Pollution Control, 2024)
For the objective of creating energy plans, setting baselines for objectives, tracking the adoption and performance of policy measures, and luring investment, it is important to have access to fast, accurate, and reliable data on renewable energy. Practical and forward-thinking energy plans are built on a foundation of sound data. This study offers a thorough examination of worldwide trends in renewable energy, taking into account the state of affairs at the moment, emerging technologies, existing frameworks for regulation, and anticipated future advancements. It emphasizes how vital renewable energy is to reducing global warming, improving energy security, and promoting sustainable development. Focus topics include solar, wind, hydro, and bioenergy, along with insights into market dynamics and regional alterations. In addition, the essay discusses the opportunities and challenges of moving toward a sustainable energy future. The report emphasizes how crucial it is for government regulations, investor dynamics, and developments in technology to propel the renewable energy industry. In spite of obstacles like undefined regulations and limited infrastructure, renewable energy has a bright future ahead of it, with significant growth anticipated and lots of room to develop. According to the study's findings, renewable energy will be essential to the world's energy transition and to the growth of sustainable energy sources in the future
Keywords: Geothermal; Global Warming; Ocean Energy; Wind Energy; biomass